Resistance training prevents the reduction of insulin-mediated vasodilation in the mesenteric artery of dexamethasone-treated rats. - JOÃO E.S. ARAUJO; FABRÍCIO N. MACEDO; DAVI P.M. OLIVEIRA; RAQUEL M. BRITTO; JULLYANA S.S. QUINTANS; ROSANA S.S. BARRETO; MARCIO R.V. SANTOS; LUCINDO J. QUINTANS-JUNIOR; ANDRÉ S. BARRETO (Anais da Academia Brasileira de Ciências, 2020)
Abstract This study evaluated whether resistance training (RT) could prevent glucocorticoid-induced vascular changes. Wistar rats were divided into groups: control (CO), dexamethasone (DEX), and Dexamethasone+RT (DEX+RT). On the eighth week, dexamethasone was administered in the DEX and DEX+RT groups. Thereafter, the animals were sacrificed and blood samples were used to assess the lipid profile, glucose and insulin. Vascular reactivity to insulin and phenylephrine (Phe) were evaluated. The DEX+RT group presented an improvement in the lipid profile, fasting glucose, and insulin levels compared to the DEX group. In addition, vasodilation was reduced in the DEX group compared to the CO group, and was increased in the DEX+RT group. After inhibition of phosphatidylinositol 3-kinase, DEX group showed contraction, in which it was in the DEX + RT group. When nitric oxide synthase (NOS) participation was evaluated, the DEX group presented a contraction compared to the CO group, with no contractile effect in the DEX+RT group. Moreover, vasoconstriction caused by NOS inhibition was abolished by BQ123 (endothelin receptor antagonist). In respect Phe response, there was an increase in tension in the DEX group compared to the CO group, being reduced in the DEX+RT group. The results suggest that RT prevented damage to vascular reactivity.